High‐Performance Oxygen Reduction Electrocatalyst Derived from Polydopamine and Cobalt Supported on Carbon Nanotubes for Metal–Air Batteries. (9th February 2017) - Liu, Yiling; Chen, Fengjiao; Ye, Wen; Zeng, Min; Han, Na; Zhao, Feipeng; Wang, Xinxia; Li, Yanguang
Abstract : The development of nonprecious metal‐based electrocatalysts for the oxygen reduction reaction holds the decisive key to many energy conversion devices. Among several potential candidates, transition metal and nitrogen co‐doped carbonaceous materials are the most promising, yet their activity and stability are still insufficient to meet the needs of practical applications. In this study, a core–shell hybrid electrocatalyst is developed via the self‐polymerization of dopamine and cobalt on carbon nanotubes (CNTs), followed by high‐temperature pyrolysis. The polymer‐derived carbonaceous shell contains abundant structural defects and facilitates the formation of CoN/C active sites, whereas the graphitic carbon nanotube core provides high electrical conductivity and corrosion resistance. These two components separately fulfill different functionalities, and jointly afford the catalyst with excellent electrochemical performance. In 1m KOH, CoN/CNT exhibits a positive half‐wave potential of ≈0.91 V, low peroxide yield of <7%, as well as great stability. When used as the air catalyst of primary Zn–air and Al–air batteries, this hybrid electrocatalyst enables large discharge current density, high peak power density, and prolonged operation stability. Abstract : CoN/carbon nanotube core–shell hybrid electrocatalyst is developed via the self‐polymerization of dopamine and cobalt on carbon nanotubes followed by high‐temperature pyrolysis. It exhibits an excellent electrocatalytic activity for the oxygen reduction reaction, and can serve as the air catalyst to enable high‐performance primary Zn–air and Al–air batteries.